Enantioselective synthesis of isochromans and tetrahydroisoquinolines by C–H insertion of donor/donor carbenes. Issue 2 (27th November 2019) - Nickerson, Leslie A.; Bergstrom, Benjamin D.; Gao, Mingchun; Shiue, Yuan-Shin; Laconsay, Croix J.; Culberson, Matthew R.; Knauss, Walker A.; Fettinger, James C.; Tantillo, Dean J.; Shaw, Jared T.
Abstract : Six-membered ring oxygen and nitrogen heterocycles are formed stereoselectively by C–H insertion of donor/donor carbenes. Abstract : Reports of C–H insertions forming six-membered rings containing heteroatoms are rare due to Stevens rearrangements occurring after nucleophilic attack on the carbene by a heteroatom. Using donor/donor carbenes and Rh2 ( R -PTAD)4 as a catalyst, we have synthesized a collection of isochroman substrates in good yield, with excellent diastereo- and enantioselectivity, and no rearrangement products were observed. Furthermore, we report the first synthesis of six-membered rings containing nitrogen by C–H insertion to form tetrahydroisoquinolines. In one case, a Stevens rearrangement product was isolated at elevated temperature from a carbamate-protected amine substrate and computational evidence suggests formation through a free ylide not bound to rhodium.